Etyka w ekonomicznych badaniach naukowych - Wyżnikiewicz, Bohdan (Annales. Etyka w Życiu Gospodarczym, 2008)
The paper summarizes the author’s experience of conducting economic scientific research. Economic scientific research is understood as both an analysis of economic phenomena and research purchased on the market of research services. The former are not subject to ethical dilemmas. It is a professional approach backed by sound economic theory that is important. The latter, regardless of who purchases research services, pose a risk of ethical dilemmas and conflicts of interest. The area of potential risk is connected to expectations of organizations purchasing research services. In most cases organizations are interested to receive objective assessments or recommendation necessary to take decisions. Ethical conflict appears when the destination of research is lobbing or a company’s image creation. The results of research may be used as an instrument of competition. It is thus vital that a research organization should judge the ethical dimension of undertaken research tasks. Research projects being socially beneficial should be definitely undertaken. In controversial cases, the conviction of the rightfulness in the ethical dimension ought to be decisive. In all cases the principal rule should be aiming at achieving scientifically objective assessments and opinions.